Family of Site-Selective Molecular Optical Switches - Sakata, Tomoyo (2005)
[Image: see text] We describe the design, synthesis, and characterization of a family of thiol-reactive optical switches for labeling proteins and other biomolecules. Site-selective introduction of photochromic probes within biomolecules is being used as part of a new approach for optical control of biomolecular interactions and activities within cells. The thiol-reactive photochromic probes described in this report include a spironaphthoxazine and five spirobenzopyrans. The location of the thiol-reactive group on the spirobenzopyran is different for each probe; this feature can be used to control the geometry of the optical switch within a bioconjugate. The photochromes undergo rapid and reversible, optically driven transitions between a colorless spiro (SP) state and a brightly colored merocyanine (MC) state. The MC absorption of a spironaphthoxazine conjugate is red shifted by more than 100 nm compared to the equivalent spirobenzopyran, which may be exploited for the independent control of the MC to SP transition for up to two different spironaphthoxazine and spirobenzopyran conjugates within the same sample.